Generalized Core Functions of Maximum Entropy Theory of Ecology (European Journal of Pure and Applied Mathematics, 2024)
Core distributions of Maximum Entropy Theory of Ecology (METE) are the Spatial Structure Function (SSF) and the Ecosystem Structure Function (ESF). SSF is a by-species prediction of the clustering of individuals over space. ESF is a kind of container function that describes the probability space of how abundances are assigned to species and how metabolic energy is parti-tioned over individuals in a community. In this study, these core functions of METE are generalized by deriving the corresponding functions in the Tsallis q-entropy. Derivation used the method of Lagrange multipliers. The generalized SSF and ESF are expressed in terms of the q-exponential function. Numerical examples are provided to illustrate the generalized SSF.
Keywords: Probability Distribution; Ecology; Entropy; Tsallis Entropy; Spatial Structure Function; Ecosystem Structure Function